Producing Spatial Distribution Maps and Analyzing Spatial Efficiency of Fire Stations Using GIS for Confronting Natural Disasters: Study area, Latakia city - إياد عباس; فادي شعبان; ربا جديد (Latakia University Journal -Engineering Sciences Series, 2023)
This paper presents a proposed prototype model for a geodatabase as an essential step in disaster management. This geodatabase includes spatial and attribute data, and then all this information were organized in layers within the geographic information systems (GIS) environment. Firstly, the three models of the proposed geodatabase were designed: conceptual model, logical model, and physical model. Accordingly, the efficiency of the spatial distribution of fire stations in the city of Lattakia was measured due to the modern methods that the GIS environment enjoys in analyzing spatial data for various fields. This study was carried out by identifying unserved areas by applying three international standards represented by (the geographical standard, the speed of response time, and the demographic standard), in addition to the use of quantitative methods, which contribute to determining the extent of the coverage efficiency of these centers in relation to the affected sites as a result of a hypothetical earthquake scenario., and suggesting new suitable places in case it turns out to be insufficient. Depending on the ArcGIS Network Analyst extension, this data was managed and evaluated statistically for the purpose of identifying some important points in order to improve the fire service provided in the city. The study reached a number of results, the most important of which are: the need for a unified geodatabase at the level of Lattakia city , constantly updated, and from which we can obtain data related to disaster management, and it was found that the spatial distribution of fire stations services is not commensurate with the three criteria studied, and additional centers were proposed to cover the entire city in proportion to the population and area.